2014
DOI: 10.1080/00268976.2014.960494
|View full text |Cite
|
Sign up to set email alerts
|

Geometric model-based fitting algorithm for orientation-selective PELDOR data

Abstract: Pulsed electron-electron double resonance (PELDOR or DEER) spectroscopy is frequently used to determine distances between spin centres in biomacromolecular systems. Experiments where mutual orientations of the spin pair are selectively excited provide the so-called orientation-selective PELDOR data. This data is characterised by the orientation dependence of the modulation depth parameter and of the dipolar frequencies. This dependence has to be taken into account in the data analysis in order to extract dista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 35 publications
(72 reference statements)
3
43
0
2
Order By: Relevance
“…41 Previous analysis on Cu···Cu systems has shown that, under these conditions, the Pake pattern will always contain a contribution from the perpendicular component of the dipolar coupling and therefore extraction of a distance distribution using Tikhonov regularization will always yield a distance peak at the true inter-copper distance although other peaks may also be present in the distance distribution at shorter distances. In the Tikhonov analysis of the data presented here, the distance distributions yielded only one major peak at the distance expected from molecular modeling, indicating that the effects of orientation selection 4246 are negligible. In addition, data were obtained in different positions of the g ⊥ component of the spectrum and resulted in identical distances and distance distributions ( cf.…”
Section: Resultsmentioning
confidence: 61%
“…41 Previous analysis on Cu···Cu systems has shown that, under these conditions, the Pake pattern will always contain a contribution from the perpendicular component of the dipolar coupling and therefore extraction of a distance distribution using Tikhonov regularization will always yield a distance peak at the true inter-copper distance although other peaks may also be present in the distance distribution at shorter distances. In the Tikhonov analysis of the data presented here, the distance distributions yielded only one major peak at the distance expected from molecular modeling, indicating that the effects of orientation selection 4246 are negligible. In addition, data were obtained in different positions of the g ⊥ component of the spectrum and resulted in identical distances and distance distributions ( cf.…”
Section: Resultsmentioning
confidence: 61%
“…The exact expression of the RIDME background is still missing in the literature but, as was shown in earlier reports, [30,49] a stretched exponential function or ap olynomial function can yield ag ood approximation of this background. This optimization problem was solved using ag enetic algorithm [58] that was implemented in ah ome-written program DipFit (Chapter 5i nt he Supporting Information). [38] The same program was also used to divide the original RIDME time trace by the background function and then to perform fast Fourier transformation (FFT) of the background-free time trace.…”
Section: Ridmed Ata Analysismentioning
confidence: 99%
“…In the time traces, up to 7f ull periods of ad ampened dipolaro scillation were observed with modulation depthso fu pt o2 4%.D ifferencesb etween the traces clearly indicateo rientation selection. [19][20][21][72][73][74][75][76] For the orange and green time traces, the detection pulses werer esonant with the lower field edge of the EPR spectrum,inw hich the g xx component of the g tensorh ad ar elativelyl arge contribution to the excited orientations. In theset wo traces and their corre-spondingf requency domain spectra ( Figure 3C), al arge 3.6 MHz frequency component was observed.…”
Section: Epr Measurementsmentioning
confidence: 99%